2021
DOI: 10.3892/ijo.2021.5179
|View full text |Cite
|
Sign up to set email alerts
|

Underlying metastasis mechanism and clinical application of exosomal circular RNA in tumors (Review)

Abstract: Circular RNA (circRNA) is a long non-coding RNA molecule with a closed loop structure lacking a 5'cap and 3'tail. circRNA is stable, difficult to cleave and resistant to RNA exonuclease or RNase R degradation. circRNA molecules have several clinical applications, especially in tumors. For instance, circRNA may be used for non-invasive diagnosis, therapy and prognosis. Exosomes play a crucial role in the development of tumors. Exosomal circRNA in particular has led to increased research interest into tumorigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 113 publications
0
17
0
Order By: Relevance
“…Compared with other types of competing endogenous RNAs, circRNAs have the following advantages. First, circRNAs are not easily degraded by RNA enzymes (RNase or RNA exonucleases)[ 21 , 22 ], which makes the circRNA structure stable and enables the possibility to stably inhibit the performance of miRNA function, with a stronger adsorption capacity for miRNAs than linear mRNAs and long noncoding RNAs. Second, existing studies have shown that the majority of circRNAs are highly expressed and that they can contain substantial miRNA response elements in a single molecule[ 23 - 25 ]; therefore, circRNAs are able to instantly bind or release large amounts of miRNAs to efficiently exert their regulatory roles.…”
Section: Biological Functions Of Circrnasmentioning
confidence: 99%
“…Compared with other types of competing endogenous RNAs, circRNAs have the following advantages. First, circRNAs are not easily degraded by RNA enzymes (RNase or RNA exonucleases)[ 21 , 22 ], which makes the circRNA structure stable and enables the possibility to stably inhibit the performance of miRNA function, with a stronger adsorption capacity for miRNAs than linear mRNAs and long noncoding RNAs. Second, existing studies have shown that the majority of circRNAs are highly expressed and that they can contain substantial miRNA response elements in a single molecule[ 23 - 25 ]; therefore, circRNAs are able to instantly bind or release large amounts of miRNAs to efficiently exert their regulatory roles.…”
Section: Biological Functions Of Circrnasmentioning
confidence: 99%
“…CircRNAs are mainly produced by exon cyclization, and while some circRNAs can also be derived from introns, antisense RNAs and 5′ or 3′ untranslated or intergenic genomic regions ( Guo et al, 2022 ). Sanger first identified the structural characteristics of circRNAs, which consist of a single-stranded, highly stable and closed loop structure lacking a 5’cap or 3’poly-A tail ( Wei et al, 2021 ). Unlike conventional forward splicing, circRNAs originate from the same precursor as linear RNA transcriptsto form circular RNAs, which is named as back-splicing ( Vromman et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to miRNAs, circRNAs are more stable and not easily degraded by exonucleases. CircRNAs are involved in various cancer-related physiological cellular processes and are recognized as potential biomarkers in cancer metastasis ( Li and Yang, 2021 ; Wei et al, 2021 ; Yarmishyn et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%